The problem of overcoming Kazakh non-equivalence in literary translation: a review of research and approaches - Burkitbayeva, Zh.M. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article analyses the work of local researchers studying the issue of Kazakh non-equivalence. It examines the ways of overcoming non-equivalence in the literary translation of works of Kazakh authors into Russian and English. A review of the key works published in international and local scientific journals over the past five years, from 2020 to 2024 inclusive, is provided. The relevance of the study is determined by the need to preserve the cultural and aesthetic features of the original text when adapting it for a reader in another linguocultural environment. The article focuses on the need for a careful approach to the transfer of non-equivalent vocabulary in the process of literary translation. Based on the full-text analysis and synthesis of the results, it can be concluded that various methods, such as transcription, transliteration, calque, descriptive translation, explanatory footnotes, approximate translation, replacement, and omission, can be used to convey Kazakh non-equivalent vocabulary in literary translation into Russian and English. In the future, we suggest conducting research on how the target audience perceives the translation.